GAMBARAN PENANGANAN PASIEN GAWATDARURAT DI INTALASI GAWAT DARURAT RUMAH SAKIT SANTA ELISABETH MEDAN - Rusmauli Lumban Gaol (STIKes Santa Elisabeth Medan, 2018)
Emergency is a condition in which someone needs immediate treatment or help because if he does not get first aid quickly it will threaten his soul or cause permanent disability. Patients of emergency are brought to Emergency Installation. Emergency Installation is the spearhead of the hospital where all incoming patients will be handled on this unit. The scope of emergency services is to conduct a primary survey, such as airway, breathing, circulation, disability and secondary survey. Goals:The purpose of this study is to find out the handling of Emergency patients at the Emergency Installation of Santa Elisabeth Hospital Medan in 2017 Methods:The research design used was descriptive. The population used was emergency patients, with sampling technique of pulposive sampling of 297 people. The criteria used were inclusion with the criteria of an acute myocardial infarction patient, head trauma, airway obstruction, pneumothorax, burns and shock Results:Technique used by researcher was documentation study with the results of the study showed male gender of 176 people (59.3%), age> 65 years were 98 people (33%) Handling of the case of the highest emergency patients was acute myocardial infarction 98 people (33%). Conclusion: The conclusion shows that male patients tend to suffer from heart disease. Age> 65 years is age that susceptible to disease because of the lack body system work such as heart